TO THE QUESTION OF THE CHRISTIAN DOCTRINE IN THE NOVEL “CRIME AND PUNISHMENT” BY F.M. DOSTOEVSKY - MIJIFERJYAN, TEREZA (Bulletin of Yerevan University H: Russian Philology, 2019)
The article raises the question of Christianity, the very person of Christ and the attitude to the world order through the prism of faith. Dostoevsky's Christ is not just an attribute of the Christian faith, but is an unshakable example of love to neighbor. It is in this aspect that the author considers the attitude of Sonya, Marmeladov and Raskolnikov to Christianity.
Keywords: Dostoevsky, “Crime and Punishment”, Christian doctrine, Marmeladova, epilogue